Sporocadaceae species associated with grapevine trunk diseases in Cyprus - Makris, Georgios; Kanetis, Loukas; Christoforou, Michalakis (My University, 2022)
Grapevine trunk diseases (GTDs) are biotic factors that threaten economic sustainability of grape indus-tries. Besides well-known diseases, there is increased interest in wood-colonizing fungi that infect grapevine woody tissues, and new species are being described as GTD causal agents. More than 140 fungal species have been reported in association with GTDs, but the degree of involvement for many GTD-related species remains to be elucidated. In 2017, during a survey conducted in Cyprus, wood samples were collected from vines exhib-iting typical GTD symptoms, including decline, and dead cordons and spurs. Based on morphological and multilocus phylogenetic analyses (ITS, LSU, TEF1, and TUB2), four species of Sporocadaceae were found in association with GTDs, including Seimatosporium mari-vanicum and Se. vitis-viniferae, and Sporocadus kurdis-tanicus and Sp. rosigena. Pathogenicity trials with seven selected isolates, representative of each species, were conducted on woody stems of 2-year-old potted grape-vines (‘Xynisteri’). All the isolates were pathogenic, caus-ing dark brown to black vascular discolouration of wood tissue below the bark, extending upward and downward from the points of inoculation. The Sporocadus isolates (mean lesion length 6.9 to 9.2 cm) were more aggressive than Seimatosporium isolates (4.0 to 4.1 cm). Re-isola-tion percentages of the inoculated pathogens were 40% for Se. marivanicum, 35–67% for Se. vitis-viniferae, 28 - 44% for Sp. Kurdistanicus, and 25–32 % for Sp. rosigena. This is the first report of Se. marivanicum, Sp. kurdistan-icus and Sp. rosigena causing symptoms on Vitis vinifera in Europe, and suggesting a potential role for Sporoca-daceae in the GTD complex.
Keywords: Grapevine Trunk Diseses; Sporocadaceae